Kesesuaian Lahan Untuk Pengembangan Ekowisata Mangrove di Kawasan Ekosistem Esensial (KEE) Tanjung Boleu Desa Kao Kabupaten Halmahera Utara - Yakub Dimon; Ramli Hadun; Adnan Sofyan (Universitas Khairun, 2022)
Mangrove ecotourism is one of the uses of mangrove forests from an economic perspective to achieve prosperity. In addition, Ekowista directly has the benefit of nature and environmental conservation. KEE Esential ecosystem area in an areathat has important value for consevation outside the coservation area. Functions sunc as consevation of life support system, preservation of biologicalÂ divercity and sustainable use. This study aims to identify the potential of KEE mangrove ecotourism land, evaluate the feasibility of the area and formulate the concept of a KEE mangrove ecotourism development strategy. The methods used are survey methods, interviews and literature studies. The approach used is descriptive qualitative and SWOT analysis.The results showed that the ecotourism potential in KEE Tanjung Boleu, Kao Village, met the requirements for both physical, biological and socio-cultural potential. This type of research is quantitative-qualitative. The quantitative approach in this research is the type of research using tabulated data or numerical data as comparison material and reference material in analyzing. The analytical tool used in this study is an analysis of the suitability of ecotourism land for mangrove classification and also a strategy analysis or SWOT. Then the qualitative approach in this study, namely non-mathematical research with the process of generating data from the findings in the form of collecting respondents' opinions. From the results of the ecotourism land suitability analysis test in Tanjung Boleu, Kao Village, assessed based on the parameters of ecotourism land suitability for mangrove classification, it shows that this area is suitable for its designation as a tourist attraction. Then the right strategy for its development is the strategy of utilizing strengths to get opportunities